COMPUTER-SUPPORTED COLLABORATIVE WORK BERLANDASKAN TEORI AKTIVITAS, SERTA USAHA MENINGKATKAN COLLABORATIVE AWARENESS - Michael Iskandar (Bina Ekonomi, 2007)
Computer-supported Cooperative Work (CSCW) is a concept that emphasizes the collaborative aspect in information technology applications. A great many CSCW systems have been developed so that Schill, for example, cites no less than ten different classification foundations. The many choices available can be very confusing for the management of an organization that wishes to implement CSCW.One of the features that must be set up by CSCW software producers is collaboration awareness, which is the ability of the software to "know" that it is being used by several people at the same time. Research shows that there have been efforts to create collaboration awareness not only of the software, but also of the user. One of these efforts is to display the social activity awareness in a CSCW session.